Dried Blood Spots for Measuring Vibrio cholerae-specific Immune Responses. - Anita S Iyer; Andrew S Azman; Malika Bouhenia; Lul O Deng; Cole P Anderson; Michael Graves; Pavol Kováč; Peng Xu; Edward T Ryan; Jason B Harris; David A Sack; Francisco J Luquero; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Vibrio cholerae causes over 2 million cases of cholera and 90,000 deaths each year. Serosurveillance can be a useful tool for estimating the intensity of cholera transmission and prioritizing populations for cholera control interventions. Current methods involving venous blood draws and downstream specimen storage and transport methods pose logistical challenges in most settings where cholera strikes. To overcome these challenges, we developed methods for determining cholera-specific immune responses from dried blood spots (DBS). METHODOLOGY/PRINCIPAL FINDINGS:As conventional vibriocidal assay methods were unsuitable for DBS eluates from filter paper, we adopted a drop-plate culture method. We show that DBS collected from volunteers in South Sudan, and stored for prolonged periods in field conditions, retained functional vibriocidal antibodies, the titers of which correlated with paired serum titers determined by conventional spectrophotometric methods (r = 0.94, p = 0.00012). We also showed that eluates from DBS Serum Separator cards could be used with conventional spectrophotometric vibriocidal methods, and that they correlated with paired serum at a wide range of titers (r = 0.96, p<0.0001). Similarly, we used ELISA methods to show that V. cholerae O-specific polysaccharide antibody responses from DBS eluates correlated with results from paired serum for IgG (r = 0.85, p = 0.00006), IgM (r = 0.79, p = 0.00049) and IgA (r = 0.73, p = 0.0019), highlighting its potential for use in determination of isotype-specific responses. Storage of DBS cards at a range of temperatures did not change antibody responses. CONCLUSION:In conclusion, we have developed and demonstrated a proof-of-concept for assays utilizing DBS for assessing cholera-specific immune responses.